Comparative Statistical Analysis - عبد الله سهيل نجم; محمد نبيل صالح (Journal of Economics and Administrative Sciences, 2013)
In this paper, a statistical analysis compared the pattern of distribution of spending on various goods and services and to identify the main factors that control the rates of spending between the survey of social and economic status of families in Iraq for the year (2007) and the survey of Iraq knowledge net work (IKN) for the year (2011), which were carried out by the Central Bureau of Statistics through the use of factor analysis and cluster analysis, using the ready statistical software package ready (SPSS) to gain access to the results.